Frequency of Leptospira spp in pigs from commercial farms and backyard breeding slaughtered in two abattoirs of Lima - Anampa V., Luis (2012)
The objective of this study was to determine the frequency of antibodies against Leptospira spp in pigs reared in five well-managed farms (n=163) and from 11 backyard breeding (n=133) owners in the Lima valley, Peru. Blood samples (n=296) were collected in two slaughterhouses for antibody detection against eight serovars of Leptospira by microaglutination test. The 85.8 ± 3.9% (254/296) of samples had antibodies against one or more serovars of Leptospira. The 89.6 ± 4.7% (146/163) and 82.1 ± 6.5% (108/133) of samples from well-managed farms and from backyard breeding pigs showed antibodies against Leptospira spp. The serovars icterohaemorrhagiae, pomona, and georgia were the most frequently detected in both groups of pigs. No antibodies were detected against serovars bratislava and grippothyphosa. Antibody titres ranged from 100 to 400, being the highest titles (800 to 1600) detected more frequently in backyard breeding pigs. Serovars icterohaemorrhagiae and pomona were the most common mixed infections found for both type of breeding systems. There were no association between antibodies against Leptospira and type of pig breeding system.